Pertimbangan Lingkungan pada Pembangkit Listrik Tenaga OTEC (Ocean Thermal Energi Conversion) - Andi Hendrawan (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2019)
Indonesia, which has the largest population among ASEAN countries, soit will become net oil imports at the beginning of the 21st century. TheIndonesian government has developed a long-term energy plan that aimsto diversify energy to reduce the country's dependence on oil. Onerenewable energy source is utilizing differences in sea surfacetemperature, solar energy that creates this gradient and specificallyOcean Thermal Energy Conversion (OTEC) Ammonia is formed by acatalytic combination of 3 moles of hydrogen with 1 mole of nitrogen athigh pressure and medium temperature with an iron oxide catalyst. theenvironmental impact of a closed cycle OTEC can be understood. Thefollowing have been identified as potentially significant: release of fluidsor biocides that work in the atmosphere, impacts on threatened orendangered terrestrial or marine species, etc. Because of its irritation,these pollutants can stimulate the inflammatory process in the upperrespiratory tract, which is the channel of exposure from the nose to thethroat